Competitividade e gestão de sistemas de informações: um estudo de caso de instituições de ensino superior - Palaia, Ronaldo Tavano (2001)
The aim of this project is to show the intimate relationship between the competitively of Organizations and the Management Information Systems. First studies the environmental aspects that respond for the existence of the organizations trying to characterize the technology as a fundamental link at the evolutive process of socialization. The conceptual aspects analyzed into the introduction are seeing trough the last decades, showing up the techno-economical-social and cultural phenomena that are responsible for business changes pointing out the movements and tendencies that draw a Global Panorama of increasing competitiveness. Then presents a proposal of an Organizational Model of systemic nature that respond with adequacy to nowadays fast changes. After this develops a study of the data systems, the managements of data systems and its relationship with the competitiveness of the organizations. According to actual economic environment draws a case study of the influence of the management of data systems at the competitiveness of organizations of knowledge more specifically of the Universitary institutions.